Familial predisposition of thoracic outlet syndrome: does a familial syndrome exist? Report of cases and review of literature. Issue 3 (4th May 2021) - Goeteyn, Jens; Pesser, Niels; van Nuenen, Bart; van Sambeek, Marc; Teijink, Joep
Abstract: Introduction: Neurogenic thoracic outlet syndrome (NTOS) is caused by compression of the brachial plexus. The clinical presentation of NTOS is characterized by symptoms of pain, paresthesia, numbness or muscle weakness in the neck, arm or hand. Methods: In this case report, five patients were diagnosed with NTOS. They all had a first degree relative with NTOS as well. Conlusions: These cases show familial predisposition in thoracic outlet syndrome. Could a form of familial TOS exist?